Enhancing Organizational Well-being and Employee Health: Strategic and Holistic Approaches for Primary and Allied Healthcare Providers - Alipio, John N.; Cacatian, Rona R.; Corpus, Roland Azel F.; Ronquillo, Christine Angeli M.; Sarmiento, Isabelle S.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The purpose of this study is to identify and evaluate effective strategies for enhancing organizational well-being and employee health among prima-ry and allied healthcare providers in the Philippines, with a focus on develop-ing holistic approaches that address both physical and mental health needs.Recognizing the value of employee well-being in the healthcare sector, in-stitutions are looking for ways to improve employees’ overall health and well-being and subsequently increase their job satisfaction and productivity.This study will assess the strategies and effectiveness of implementing different health promotion programs among primary and allied healthcare providers in the Philippines across different sectors to enhance employee well-being and contribute to organizational productivity and success. This study will assess different areas of employee well-being, such as stress man-agement, mental health support, physical health promotion, and work-life balance. These programs may include a variety of wellness initiatives, such as fitness classes, mental health awareness seminars, health screenings, stress management workshops, and flu vaccination drives. Organizations may build a supportive work environment that promotes employee satisfac-tion, resilience, and optimal performance by understanding the unique is-sues that healthcare professionals confront and implementing focused inter-ventions and targeted solutions.This study will look for effective techniques that can be adjusted to the specific needs of healthcare institutions in the Philippines. The findings will be useful for politicians, healthcare administrations, and human resource officers looking to improve employee well-being and, as a result, patient care quality.